2021
DOI: 10.1155/2021/6659106
|View full text |Cite
|
Sign up to set email alerts
|

A New Pyrrolidone Alkaloid and Other Constituents from Rourea oligophlebia Stems

Abstract: Phytochemical study of Rourea oligophlebia stems led to the isolation of a new 2-pyrrolidone alkaloid (R,S)-N-(5-hydroxyl-pyrrolidin-2-one-1-yl)acetamide (1), together with 14 known compounds including friedelin (2), friedanol (3), taraxerol (4), vanillin (5), coniferyl aldehyde (6), apigenin (7), 7α-hydroxy-3β-sitosterol (8), coniferyl alcohol (9), scopoletin (10), emodin (11), protocatechuic acid (12), catechin (13), procyanidin A1 (14), and (E)-2,3,5,4’-tetrahydroxystilbene-2-β-D-glucoside (15). Several iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…In addition, the genus Rourea is also commonly used in traditional medicine such as R. regusa root for respiratory diseases, R. concolor for kidney disease, and R. mimosoides for bloody diarrhea treatments [10] . Previous studies indicated that the secondary metabolites from R. oligophlebia have antibacterial and cytotoxic properties [9,11] . These results may assist in prescribing oriental traditional medicine, although there is no further scientific evidence from this species.…”
Section: Introductionmentioning
confidence: 96%
“…In addition, the genus Rourea is also commonly used in traditional medicine such as R. regusa root for respiratory diseases, R. concolor for kidney disease, and R. mimosoides for bloody diarrhea treatments [10] . Previous studies indicated that the secondary metabolites from R. oligophlebia have antibacterial and cytotoxic properties [9,11] . These results may assist in prescribing oriental traditional medicine, although there is no further scientific evidence from this species.…”
Section: Introductionmentioning
confidence: 96%